I need som help with this.
Im having trouble finding the derivative of (the first image 1.)
The Answer should be (image 2)
But all I get is (image 3)
Were does the √(x-1) come from?
THANKS
Hi
$\displaystyle f(x) = (x-4) \: \sqrt{x-1}$
To find the derivative use the formula of the derivative of a product
$\displaystyle (uv)' = u'v + uv'$
Here
$\displaystyle u(x) = x-4$ then $\displaystyle u'(x) = 1$
$\displaystyle v(x) = \sqrt{x-1}$ then $\displaystyle v'(x) = \frac{1}{2\sqrt{x-1}}$
Therefore
$\displaystyle f'(x) = \sqrt{x-1} + \frac{x-4}{2\sqrt{x-1}}$